Analisis Deskriptif Implementasi Pembelajaran Daring Terhadap Tingkat Kemandirian Belajar Mahasiswa di Era Digital (Indo-MathEdu Intellectuals Journal, 2025)
The transformation of learning in the digital era has accelerated the adoption of online systems in higher education, requiring students to develop self-directed learning skills. This study aims to describe the implementation of online learning and the level of students’ learning autonomy based on their perceptions. A descriptive quantitative approach was employed, involving 100 undergraduate students from various study programs who had participated in online learning for at least two semesters. Respondents were selected using purposive sampling based on these criteria. Data were collected through a five-point Likert scale questionnaire and analyzed using descriptive statistics. The results indicated that time flexibility was the most appreciated aspect of online learning, followed by content clarity and the use of technology. Conversely, independent learning motivation received the lowest mean score (3.82), highlighting challenges in maintaining intrinsic motivation without direct supervision. These findings affirm that the success of online learning depends not only on digital infrastructure but also on strengthening affective and motivational aspects as well as adaptive instructional design. The implications underscore the importance of pedagogical strategies that foster learner autonomy, meaningful interaction, and emotional support to enhance the long-term effectiveness of online learning.